MELAWAN DENGAN UANG : EKSISTENSI UANG REPUBLIK INDONESIA PROVINSI SUMATERA (URIPS) TERHADAP PEREDARAN UANG NICA DAN JEPANG DI SUMATERA 1947-1949 - Abdullah, Abdullah; Junaidi, Teuku; Harahap, hanif (Program Studi Pendidikan Sejarah - Universitas Samudra, 2021)
Money plays a role in maintaining the independence of the Republic of Indonesia. At the beginning of Indonesia's independence, NICA, which wanted to regain control of Indonesia, carried out various strategies, including by disrupting the monetary economy of Indonesia. By circulating the NICA currency and the Japanese currency indefinitely. Therefore, Indonesia created Oeang Republik Indonesia (ORI). However, it was unable to distribute to various regions. This was due to the blockade of the NICA army and at the same time wanting to destroy the printing of ORI money. At that time, the Government made a mandate to print URIDA money in every region. Sumatra, which at that time printed the Money of the Republic of Indonesia in the Province of Sumatra (URIPS). used as a legal medium of exchange for the people of Sumatra. And at the same time being a means of resistance to the circulation of NICA money and Japanese money in Sumatra. In the declaration it was stipulated that the URIPS was valid in all parts of the island of Sumatra as a legal means of payment. So that URIPS continued to exist among the Sumatran community in 1947-1949.